Rancang Bangun Sistem Informasi Pendataan Alumni Pada STIE Prabumulih Berbasis Website Dengan Menggunakan Bootstrap - Ariansyah Ariansyah; Fajriyah Fajriyah; Febby Satryadi Prasetyo (Jurnal Mantik Penusa, 2017)
The development of information system today has led to various changes that significantly taken into account in an organization decision making to obtain precise and accurate information for use. In processing the data of alumni, STIE Prabumulih is still using computerized system. This way brings the lack of development of information includes vacancies information obtained by alumni and students which is neither accurate nor sufficient, hence it is necessary for STIE Prabumulih to have the development of information so that information obtained can be more accurated and updated. Programming language used is the Personal Hypertext Preprocessor (PHP) and design editor is Macromedia Dreamwaver CC 2015. The application also uses MySQL as its database so it can be helpful in inputting data in which it can be done   more quickly, precisely and efficiently. The study is  a descriptive design that aims to clarify the data obtained and give a detailed description of the existing alumni data collection system at STIE Prabumulih.Keywords: Alumni, website, PHP, MySQL, descriptive